APLIKASI TEKNOLOGI SARPALAM 100UF UNTUK PENYEDIAAN AIR BERSIH DI DUSUN DANTAR, PADANG CERMIN, LAMPUNG - Arie Herlambang (Jurnal Teknologi Lingkungan, 2001)
Dantar Village can be reached from Bandar Lampung in one hour. There are 250 families or around 1250 people dwell there. In Dantar, groundwater is difficult to tap, especially during dry seasons, and the water is usually turbid and salty due to hydrothermal activities at several places. Sarpalam 100 UF is the accronym of Saringan Pasir Lambat (Slow Sand Filter), which has capacity of 100 m3/day with an up flow system. Standard design for the first filtration is 6 m3/m2/day, and 4 m3/m2/day for second one, with media 1 m thickness. Sarpalam 100 UF utilizes double system is intended to keep the running even though the whole unit is being cleaned. The unit is also equippped with top and bottom flushing systems to ease maintenance. The water processed comes from Way Sanggi Rivers situated 300 m from the location of the equipment, with an elevation difference of 4,5 m. Its watercatchment uses branching porous pipe, submerged in the ground, so a constant water supply can be maintained although a flood is coming. The Sarpalam 100UF has operated for 2 months and its distribution network development is underway.